BIO-PROSPECTING VS. BIO-RESPECTING : Seeing Forests as Culturally Embedded Spaces - Naidu, Dr Maheshvari (Journal of Dharma, 2014)
The concept of ‘bio-prospecting’ refers to the activities of utilising planetary biodiversity for commercial purposes. Bio-prospecting itself has been frowned upon in (developing) countries and contexts where impoverished regulation, and both policy and ‘policing’ mechanisms are vulnerable to commercial, corporate and sometimes even, governmental manipulation. The idea of ‘selling nature to save it’ is in conflict with many communities who believe in having a more harmonious kinship with the bio-diverse natural world, through a relationship of respect and reciprocity. This essay focuses on one such community; that of traditional African diviners or sangomas and reveals their perspective of ‘bio-respecting’. The essay is positioned through the narrativised lens of the sangomas’ culturally embedded understanding of respectful harmony and represents a perspective of mutually beneficial ‘bio-respecting’.